Ketiadaan Otoritas Terpusat dalam Fenomena Kontemporer di Indonesia: :Kritik Terhadap Teori Otoritas Max Weber - Chairi, Effendi (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2019)
This article presents an analysis result on contemporary phenomenon in Indonesia by sociological approach. This states that Ulama or kiai who were formerly the only religious authorities fused religious purity in political interest. This gives negative influence for religious authority itself. Substantive divine will is forced to submit to the will of individual or certain group. So Islam which is previously inclusive and moderat melts to exclusive and discriminative acts. The distance between religious goals to rahmatan lil-’alamin and individual political interesthas been eroded (hyper-reality). Therefore, society has not trusted to the traditional authority and rational-legal authority. In actual fact, authority construction of Weber is nothing.